Feasibility Analysis of Tanjung Enim Hotel Investment in the Tanjung Enim Mining Unit Area of PT Bukit Asam Tbk - Asharyanto, Hudan; Darmansyah, Asep (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes the investment feasibility of a proposed 4-star hotel development on idle land owned by PT Bukit Asam Tbk (PTBA) in Tanjung Enim, South Sumatra, as part of the company's strategic initiative to optimize non-productive assets and diversify beyond coal mining. Utilizing a mixed-method approach, the research integrates qualitative methods such as case benchmarking, document review, and SWOT analysis with quantitative financial modeling, including Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, and Profitability Index (PI). Data were collected from both internal and external sources, including macroeconomic indicators, market trends, and comparable hotel benchmarks. Findings indicate strong legal and strategic feasibility, with the project aligned with zoning regulations and backed by full land ownership, eliminating legal uncertainties. Market analysis highlights robust demand driven by PTBA's industrial ecosystem and limited regional hotel competition. Financially, the hotel is viable with a projected NPV of IDR 17.291 billion, IRR of 14.80%, Payback Period of 8.88 years, and PI of 1.27. However, sensitivity analysis reveals significant vulnerabilities to room rates, banquet pricing, and occupancy levels. Therefore, strategic pricing, demand forecasting, and risk mitigation are essential. Overall, the project demonstrates strong investment potential, contingent upon effective operational and risk management strategies.